Secondary‐Structure‐Driven Self‐Assembly of Reactive Polypept(o)ides: Controlling Size, Shape, and Function of Core Cross‐Linked Nanostructures. Issue 32 (6th July 2017) - Klinker, Kristina; Schäfer, Olga; Huesmann, David; Bauer, Tobias; Capelôa, Leon; Braun, Lydia; Stergiou, Natascha; Schinnerer, Meike; Dirisala, Anjaneyulu; Miyata, Kanjiro; Osada, Kensuke; Cabral, Horacio; et al.
Abstract: Achieving precise control over the morphology and function of polymeric nanostructures during self‐assembly remains a challenge in materials as well as biomedical science, especially when independent control over particle properties is desired. Herein, we report on nanostructures derived from amphiphilic block copolypept(o)ides by secondary‐structure‐directed self‐assembly, presenting a strategy to adjust core polarity and function separately from particle preparation in a bioreversible manner. The peptide‐inherent process of secondary‐structure formation allows for the synthesis of spherical and worm‐like core‐cross‐linked architectures from the same block copolymer, introducing a simple yet powerful approach to versatile peptide‐based core–shell nanostructures. Abstract : Worms and spheres : Secondary‐structure‐driven self‐assembly allows for the synthesis of spherical and worm‐like architectures with cross‐linked cores from the same amphiphilic block copolypept(o)ide. By utilizing bioreversible disulfide cross‐linking, the core polarity and function are adjusted independently from particle preparation, providing a versatile biocompatible nanoparticle platform.